ANÁLISE PROTEÔMICA COMPARATIVA DO FRUTO DE CAFÉ (Coffea arabica) EM DOIS ESTÁDIOS INICIAIS DE DESENVOLVIMENTO - Bandil, Geisa Barboza (2008)
Coffee is one of the most valuable agricultural commodities, ranking second on international trade exchanges. There is much agronomic research on coffee, but molecular knowledge of its fruit development and ripening is limited. The Brazilian Coffee Genome Project provides the genomic resources required to study the proteomics of Coffea arabica, to add to results derived from DNA microarray and EST studies. This work reports a comparative proteomic investigation of immature coffee fruit in two developmental stages: stage 1, intense cell division, and stage 2, intense cell expansion. Proteins were extracted using a modified SDSPhenol method and two-dimensional electrophoresis gels stained with Coomassie blue revealed about 300 well-resolved polypeptide spots in the pH range 3-10 and 500 wellresolved polypeptide spots in the pH range 4-7. Nineteen variable polypeptides were excised, trypsin-digested and analyzed by MALDI-TOF mass spectrometry. Peptide MS data were searched against the coffee EST database and six protein spots were identified, according to their putative and assigned functions in known biosynthetic pathways: Fructose bifosfato aldolase, glyceraldehyde-3-phosphate dehydrogenase and malate dehydrogenase enzymes are part of glycolytic pathway, 11S storage globulin protein has the reserve function, the thaumatin-like protein signals a response to stress, and chloroplast precursor is involved in pathway photosynthesis. These proteins, except taumatina-like, had increased their expression at the stage of expansion of the fruit indicating that they are more required with the fruit development.